United States in Outer Space: Security Assurance and Preservation - Graham, Richard V. (2007)
Free access to-and-use of space assets by all nations in today's highly interdependent globalize society has been the long-standing policy of the United States dating back to the Eisenhower Administration. This point is espoused in the recent National Space Policy (2006) which commits to the "use of outer space by all nations for peaceful purposes and.benefit of all humanity." Yet the new policy also postures a unilateral tone and position that opposes the development of either new legal regimes or other restrictions that ".prohibit or limit US access to or use of space." Those restrictions include international arms control legislation, treaties, or resolutions that limit space weapon technology. This paper will first show how the current Space Policy is flawed by excluding multilateral diplomatic space-arms-initiatives, international cooperation, and ignores "common security" of other states. This one dimensional and self-fulfilling policy may increase asymmetrical threats to US space assets. The second part of this paper will use the recent Chinese anti-satellite test to constructively propose a basis for "non-armament treaties" using as examples the Incidents as Sea Agreements, the Bunn Initiative, and the Antarctic Treaty to forge non-threatening, transparent, confidence-building alliances that would address each state's security concerns, allow for the continuation of the United States' defensive ballistic missile defenses, and maintain for all mankind the use of outer space for peaceful purposes.